Trends in the burden of chronic diseases attributable to diet-related risk factors from 1990 to 2021 and the global projections through 2030: a population-based study - Ma, Huan; Wang, Minyan; Qin, Chu; Shi, Yun; Mandizadza, Oscar Onayi; Ni, Haojie; Ji, Conghua (Frontiers in Nutrition, 2025)
BackgroundThe global burden of diet-related chronic diseases and their future projections remain unclear. To address this gap, we present the latest data on deaths and disability-adjusted life years attributable to dietary factors from 1990 to 2021, focusing on noncommunicable diseases worldwide. Additionally, we provide predictions of mortality rates across different age groups through 2030.MethodsData from the Global Burden of Disease Study 2021 were analyzed to evaluate correlations between dietary factors and trends in chronic disease burden over a 30-year period. Moreover, we predicted the burden of chronic dietary diseases up to 2030.ResultsFrom 1990 to 2021, global age-standardized mortality rates and disability-adjusted life year (DALY) rates associated with dietary factors decreased by approximately one-third for neoplasms and cardiovascular diseases (CVDs). In high sociodemographic index (SDI) regions, neoplasm-related deaths showed a stronger correlation with dietary factors, particularly high red meat intake. In cardiovascular diseases, the leading dietary factors are low-grain diets, whereas in diabetes, it is due to increased intake of processed meat. In low-SDI regions, diets low in vegetables showed the strongest association with neoplasm-related mortality, while diets low in fruits were significantly linked to CVD and diabetes burden. High-sodium diet was a significant risk factor for CVD in the middle-SDI regions. Moreover, the 2030 projections indicated a decline in mortality from neoplasms and CVDs, with a slight increase in mortality rates from diabetes.ConclusionThe global burden of chronic diseases linked to dietary factors shows varying trends across different countries and regions, particularly influenced by their economic development levels. This variation underscores the necessity of enhancing dietary structures to mitigate chronic disease prevalence and foster overall health.